ANALISIS PELAKSANAAN PEMILIHAN KEPALA DESA ANTAR WAKTU (PAW) KABUPATEN BANYUMAS TAHUN 2022 PRESPEKTIF UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Yunita Ratna Sari; Nur Rokhanah (Governance, 2024)
This research explains the interim village head (PAW) election in Banyumas in 2022. The aim of holding the interim village head (PAW) election is to fill the vacancy in the position of village head due to death. The conditions for inter-term village head elections can be implemented because the village head dies, resigns or is dismissed and his term of office is still more than 1 year. The results of the research show that the interim village head election in Banyumas in 2022 is in accordance with Law Number 6 of 2014 concerning Villages, starting from determining the election committee, determining the permanent voter list to implementing the interim village head election which is carried out through village deliberations. Problems Interim village head elections in Banyumas district in 2022, among other things, the budget is still covered by the Village APBD and Banyumas Regent Regulation Number 70 of 2021 does not yet regulate in detail the interim village head elections. The recommendation in this research is that the Banyumas district government must realize the mandate of article 34 paragraph 6 of Law Number 6 of 2014 concerning financing for interim village head elections which are charged to the Regency/City APBD. Apart from that, the Banyumas Regency Government and the Banyumas DPRD must review Regional Regulation Number 70 of 2021.